Principal Leadership Style, Organizational Culture, Use of TIK, in Teacher Performance - Erni Erni; Iskandar Iskandar; Marwiyah Marwiyah (Budapest International Research and Critics University, 2022)
The purpose of the study was to determine the effect of the principal's leadership style, organizational culture, and use of ICT on teacher performance at SDIT Al Bina Tomoni, East Luwu RegencyUsing exploratory research with quantitative approach, Likert scale to measure variables. This study took a random sample of 50 teachers using the Slovin formula. Collecting data using a questionnaire and analyzing it using multiple regression. Some of the research variables used include the leadership style of a school principal (XI), organizational culture (X2), and the use of ICT (X3), as well as the performance of teachers (Y). The results of this study indicate that: (1) the principal's leadership style variable affects the performance of the teachers at SDIT Al Bina Tomoni, East Luwu Regency; (2) organizational culture variables have an influence on teacher performance at SDIT Al Bina Tomoni, East Luwu Regency; and (3) the use of ICT has an influence on teacher performance at SDIT Al Bina Tomoni, East Luwu Regency; (4) the variables of the principal's leadership style and the culture of the organization have a simultaneous influence on the performance of SDIT Al Bina Tomoni teachers in East Luwu district; (5) simultaneously the cultural variables of the organization and the use of ICT have an influence on the performance of teachers at SDIT Al Bina Tomoni, East Luwu district; (6) simultaneously the leadership style of the principal, the existing organizational culture and the use of ICT affect the performance of the teachers of SDIT Al Bina Tomoni, East Luwu district.